A Real-World, Prospective, Multicenter, Single-Arm Observational Study of Duloxetine in Patients With Major Depressive Disorder or Generalized Anxiety Disorder - Szekeres, Gyorgy; Rozsa, Sandor; Dome, Peter; Barsony, Gabor; Gonda, Xenia (Frontiers in Psychiatry, 2021)
Background: Suboptimal treatment response during antidepressive treatment is fairly common to the first antidepressant chosen followed by switching to another agent in the majority of cases. However, the efficacy of this strategy over continuation of the original agent is less solidly documented in ral life study. The aim of our present study was to ascertain the effects of switching to duloxetin I on general illness severity, pain, and health-related quality of life in a large sample of depressive and generalized anxiety disorder patients in a prospective, real-world, multicenter, observational study. Methods: 578 participants with major depressive disorder or generalized disorder were enrolled in 65 sites in an 8-week, 8-week, single-arm, open label, flexible-dose trial with duloxetine. Severity of symptoms (with CGI-S and CGI-I9, pain severity (with a visual analogue scale), satisfaction with current treatment and quality of life (with EQ-5D-3L) were recorded at baseline and at follow up visits 4 and 8 weeks after initiation of treatment. Data were analysed using ANOVA and mixed linear models. Results: Results indicated that severity of illness significantly decreased over the 8 weeks of the study and already at 4 weeks in both patient groups. Overall health status and all of its subindicators also significantly improved in both patient groups and so did subjective experience of pain. Satisfaction with current treatment significantly improved during the study period. Frequency of side effects was low. Among GAD patients, 2 patients dropped out of the study due to adverse effects, while in the MDD subsample, treatment was terminated due to adverse effect in 3 patients. Conclusions: This 8-week, multicenter, flexible dosing, single arm, open-label observational real-life study in major depressive disorder and generalized anxiety disorder patients switched to duloxetine after inadequate response or tolerability to other antidepressants, showed a significant positive effect on all outcome measures, including a significant decrease in illness severity as well as significant overall symptomatic improvement, with good tolerability.